2018
DOI: 10.1039/c8cp01373j
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio study of the CO–N2 complex: a new highly accurate intermolecular potential energy surface and rovibrational spectrum

Abstract: A new, highly accurate ab initio ground-state intermolecular potential-energy surface (IPES) for the CO-N2 complex is presented. Thousands of interaction energies calculated with the CCSD(T) method and Dunning's aug-cc-pVQZ basis set extended with midbond functions were fitted to an analytical function. The global minimum of the potential is characterized by an almost T-shaped structure and has an energy of -118.2 cm-1. The symmetry-adapted Lanczos algorithm was used to compute rovibrational energies (up to J … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 50 publications
1
25
0
Order By: Relevance
“…Nonetheless, as it was stated in Ref. 57, due to the method used, reduction of the basis set and too small number of grid points chosen by the authors, this PES should not be considered reliable enough to study various physical phenomena. Recently, three highly accurate PESs were reported.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
See 3 more Smart Citations
“…Nonetheless, as it was stated in Ref. 57, due to the method used, reduction of the basis set and too small number of grid points chosen by the authors, this PES should not be considered reliable enough to study various physical phenomena. Recently, three highly accurate PESs were reported.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…53,54 We recall also two very recent studies of this complex in the millimeter range, 55,56 which provided an accurate test of the recently reported PESs. 55,57,58 The theoretical investigations on the CO-N 2 complex were reviewed in more detail in a previous paper. 57 Here, we only recall the importance of the study conducted by Fišer and Polák, 59 who investigated multiple orientations of the complex using the coupled-cluster singles and doubles including connected triple corrections [CCSD(T)] and Møller-Plesset (MP) perturbation theory up to fourth order.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been demonstrated that such calculations are accurate for other Van der Waals dimers. [11][12][13][14] Probability Density (PD) and wavefunction cut plots are used to label the energy levels. We find significant coupling between in-plane and out-of-plane coordinates.…”
Section: Introductionmentioning
confidence: 99%